A educação como ferramenta de valorização do capital: uma análise a partir de O capital de Marx - Souza, Cezar Amário Honorato de (2021)
This research aims to analyse modern education in basic schools as a tool for capital replication and expansion. It also presents how such process takes place in both private and public educational institutions, by means of monetizing and selling teaching and learning to the former, and by selling commodity-like educational services for both the former and the later. Therefore, the research is going to approach some elements of greater importance: a) the teacher as a productive worker in benefit of the capital; b) the educational institution as a space for movement of the capital, considered as money-form, commodity-form and product-value; c) the unlimited capital replication in the framework of educational institutions. The final remarks underpin the fact that school education, in an ontological perspective, does not refrain from its social purpose of leading individuals to their own practices concerning social reproduction. However, regarding the social reproduction of the capital, the education in basic schools can also be considered in terms of its function as a tool for making money to the capitalist, or to the owner of the means of production. This dissertation is in line with the dialectical and historical materialism, once this theory is used as theoretical and methodological framework. The research was restricted to the theoretical-bibliographic analysis, especially the tracking of the main categories of Political Economy and education, from the work of Marx. The main references which sustain this research are the contributions of Karl Marx, specially the first and the second tomes of The Capital; the fourth tome of The Capital: The Theories of Surplus Value; and the sixth and unpublished chapter of The Capital. Nonetheless, this study also takes in other contributions, for instance, the ones put forward by Lukács and by the Brazilian researchers José Paulo Netto, Lessa, Saviani and Paro, with regards to their own differences as to how the Marxist thinking has been established in Brazil.